2010
DOI: 10.1111/j.1439-0396.2010.01068.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two probiotic additives containing Bacillus spores on carcass characteristics, blood lipids and cecal volatile fatty acids in meat type chickens

Abstract: The objective of this study was to evaluate effects of two commercially available probiotic additives, containing Bacillus spores, on carcass and meat characteristics, serum lipids and concentration of cecal volatile fatty acids of meat type chickens. Birds were fed regular corn-soy meal based feed (control), supplemented with additive A, containing 1.6 × 10(6) spores per gram of feed of Bacillus subtilis and Bacillus licheniformis (group A) or additive B, containing the same concentration of Bacillus cereus v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 47 publications
(66 reference statements)
1
13
0
Order By: Relevance
“…Similarly, in our study, males revealed higher 1‐day‐old body weight in ducklings hatched from eggs laid at 24 weeks of the duck breeder trial, especially from eggs in maternal CX+25‐OH‐D 3 ‐free group. The increased 1–14 days growth performance of males in ducklings under both of the vitamin regimens was consistent with the previous studies (Jonesa and Hughesa, ; Novak et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, in our study, males revealed higher 1‐day‐old body weight in ducklings hatched from eggs laid at 24 weeks of the duck breeder trial, especially from eggs in maternal CX+25‐OH‐D 3 ‐free group. The increased 1–14 days growth performance of males in ducklings under both of the vitamin regimens was consistent with the previous studies (Jonesa and Hughesa, ; Novak et al., ).…”
Section: Discussionsupporting
confidence: 92%
“…Nevertheless, the significant increases of TC and LDL-C in the serum were in contrast to the findings of Panda et al (2006), in which serum TC and LDL were reduced by dietary supplementation of Lactobacillus sporogenes. However, the study of Novak et al (2011) also found an enhanced serum LDL-C level. In their opinion, the lowered concentrations of cecal propionic and butyric acids in Bacillus-fed chickens might be the reason for higher levels of LDL compared with the control, because products of bacterial fermentation, specifically short chain fatty acids, may inhibit cholesterol synthesis in the plasma cholesterol in the liver (Rafter, 2002).…”
Section: Discussionmentioning
confidence: 98%
“…Toyocerin®, a preparation containing the bacterial strain Bacillus toyoi, has shown beneficial effects when administered to pigs (Jadamus et al, 2002;Stamati et al, 2006;Papatsiros et al, 2011;Kantas et al, 2014), rabbits (Brzozowski & Strzemecki, 2013), Japanese quails (Homma & Shinohara, 2004), chickens and turkeys (Jeroch et al, 2004;Grela et al, 2009;Novak et al, 2011).…”
Section: Discussionmentioning
confidence: 99%